Enhanced photocatalytic degradation of Rhodamine B employing transition metal (Fe, Cu, Co) doped ZnO/rGO nanostructures synthesized by electrospinning-hydrothermal technique - Ramos, Pierre G. (2023)
In the present work, the use of transition metal-doped zinc Oxide/reduced graphene oxide (ZnO/rGO) nanostructures for photocatalytic applications was investigated. The paper presents a novel and cost-effective electrospinning-assisted hydrothermal method of synthesizing these nanostructures onto fluorine-doped tin oxide (FTO) substrates. The research focuses on the effects of the rGO sheets attached to the ZnO nanostructure and of Fe, Cu, and Co ions as dopant transition metals. The doped ZnO/rGO photocatalysts obtained were characterized using various techniques, including Field Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive X-ray (EDX), X-Ray Diffraction (XRD), Raman spectroscopy, and Photoluminescence (PL). The results showed that the doped ZnO/rGO samples exhibited pure composition, hexagonal wurtzite structure with high crystallinity, and nanorod-like morphologies with reduced mean diameters due to doping and the rGO anchoring. Additionally, the PL experiments demonstrated that charge carrier recombination was effectively inhibited for the doped ZnO/rGO samples. The photocatalytic performances of the undoped and doped ZnO/rGO nanostructures were tested through the degradation of Rhodamine B (RhB) dye under simulated sunlight irradiation. An improvement in photocatalytic activity compared to pristine ZnO was achieved mainly due to dopants and the presence of rGO, both of which intensified the separation of photogenerated electron-hole pairs and thus hindered their recombination. The study also acknowledges some scientific challenges in controlling the doping process to achieve consistent and uniform properties. However, despite these issues, the potential applications and advantages of transition metal-doped ZnO/rGO nanostructures make them promising materials for future efficient and sustainable photocatalytic applications.